2009
DOI: 10.1177/0091270009337134
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Scaling of Therapeutic Monoclonal Antibodies: Initial Look

Abstract: The authors evaluated interspecies scaling for the prediction of human clearance of 18 therapeutic monoclonal antibodies (mAbs). Human and monkey/chimpanzee data of 14 mAbs were classified based on the targeted antigens (soluble or membrane bound). Simple allometry and/or a time-invariant method (elementary Dedrick plot) were performed. Results indicate that human clearance might be accurately predicted from monkey data for mAbs targeting soluble receptors or membrane-bound receptors with limited tissue distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 62 publications
11
125
0
Order By: Relevance
“…A fixed exponent of 0.80 was previously shown to be an appropriate singlespecies scaling factor for predicting human CL for a wide variety of therapeutic proteins and mAbs (Wang and Prueksaritanont, 2010). Other studies based on an overlapping data set of therapeutic mAbs supported use of a fixed exponent ranging from 0.75 to 0.90 to predict human CL from monkey (Ling et al, 2009;Deng et al, 2011;Dong et al, 2011;Oitate et al, 2011Oitate et al, , 2012. The range of exponents reported for mAbs is not surprising, given the relative insensitivity of this parameter toward single-species scaling between monkeys and humans (e.g., an exponent between 0.67 and 0.90 results in an approximately 2-fold change in predicted human CL).…”
Section: Discussionmentioning
confidence: 98%
“…A fixed exponent of 0.80 was previously shown to be an appropriate singlespecies scaling factor for predicting human CL for a wide variety of therapeutic proteins and mAbs (Wang and Prueksaritanont, 2010). Other studies based on an overlapping data set of therapeutic mAbs supported use of a fixed exponent ranging from 0.75 to 0.90 to predict human CL from monkey (Ling et al, 2009;Deng et al, 2011;Dong et al, 2011;Oitate et al, 2011Oitate et al, , 2012. The range of exponents reported for mAbs is not surprising, given the relative insensitivity of this parameter toward single-species scaling between monkeys and humans (e.g., an exponent between 0.67 and 0.90 results in an approximately 2-fold change in predicted human CL).…”
Section: Discussionmentioning
confidence: 98%
“…Their study of 14 mAbs indicated that, for mAbs with linear kinetics, CL in humans could be reasonably predicted from monkey data using simplified allometry with a fixed exponent. The optimal exponents were estimated to be 0.85 for soluble antigens and 0.9 for membrane-based antigens 13 . In a similar analysis of 13 mAbs with linear CL, Deng et al showed that simple allometric scaling of CL in cynomolgus monkey with an exponent of 0.85 provided a good estimate of human CL 11 .…”
Section: Discussionmentioning
confidence: 99%
“…mAb-1 (Efalizumab) Chimpanzees 6.11 (25) 0.427 (12) 0.123 (11) 2.92 (11) 0.395 (24) 0.383 (8) 3.17 (9) 0.303 (8) Patients 5.41 (13) 0.516 (21) 0.112 (11) 4.47 (9) 0.286 (18) 0.506 (11) 2.06 (9) 0.597 (6) mAb-2 (TRX-1) Baboons 32.4 (27) 398 (75) 2.04 (69) 0.931 (17) 0.84 (106) 4.57 (143) 2.04 (69)…”
Section: Application Of Translation Rules To Mab-7mentioning
confidence: 99%
“…Healthy volunteers 28.4 (24) 30.1 (15) 4.25 (12) 3.79 (11) 0.14 (100) 0.413 (85) 4.25 (12) 0.867 (14) mAb-3 (MTRX-1011A) 0.109 (7) 2.85 (16) 0.549 (13) 1.35 (21) 5.17 (4) 1.35 (2) mAb-4…”
Section: (74)mentioning
confidence: 99%
See 1 more Smart Citation